Experimental and numerical modeling of outrigger systems of tall building structures - Marabi, Bahram (2022)
The tall building’s height recently has exceeded a thousand meters. An appropriate lateral load resisting system to drift-control seems necessary. Considering that the lateral deflections play a vital role in selecting the type of tall building structures. Top-drift in tall buildings has not yet been entirely resolved for seismic demands. That is way, utilizing the structural outrigger systems is one of the most efficient structural systems to enhance the structure's lateral stiffness and minimize the top-drift without increasing the building's components sizes and mass it will need. This study aims to specify the lateral resisting responses of conventional structural outrigger models through experimental works. A new type of outrigger model was proposed to compare its effectiveness with the conventional models. Finally, to optimize the parameters affecting the new outrigger model's lateral response is proposed through the Finite Element Method (FEM). A total of eight 3D models including three types of structural core models (no outrigger), two types of single outrigger models, two types of multi outrigger models, and a proposed new outrigger model, were experimented using a quasi-static cyclic test. The models are termed the Core Models (Core-1,2 and 3), Opti-models (1-Out, 2-Out), Conv-models (Cap-Out, 2-Out), new model (DevOut) and FE Dev-Out. This research, inspired by the 2D analytical method with an idealized pattern, has been used to advance to 3D experimental modeling to achieve more reliable results. The hysteresis curves have been calculated to obtain the initial lateral stiffness, effective stiffness, ultimate lateral strength, ductility ratio, energy dissipation capacity, and failure mechanism in all experiments through the quasi-static cyclic test models. Results indicated that the outrigger systems' optimal forms failed at the first outrigger's upper level while the conventional forms and core models failed at the base. The 2-Out optimal form up to 140% have higher effective stiffness than 1- Out, and Cap-Out 36% higher than 2-Out conventional form, while the Dev-Out form is 31% higher than the 1-Out Opti model. The Cap-out 6% is higher than the 1-Out Opti form as well. The energy dissipation of the 2-Out conventional form has the highest level by 686.1 kN.mm, while the Dev-Out model has the lowest value by 297.7 kN.mm than other outrigger forms. The 2-Out conventional form by 6.73 is ductile, and the 2-Out Opti model by 3.84 ratios has a second-place than other forms. The proposed new model can increase the effective lateral stiffness by 2.2 times at the develop-outrigger location due to added outer peripheral columns. The FE Dev-Out model to reduce the top-drift was optimized when the outrigger is placed at 0.4H from the top of the model. Also, the base moment was minimized if the outrigger is placed at the mid-height and base position range. In final, the developed 3D method compared to the traditional 2D methods indicated a significant difference in the conventional outrigger forms' performance with optimal forms under lateral loads, stiffness, ductility, and energy dissipation in tall building structures.